Differential nasal swab cytology represents a valuable tool for therapy monitoring but not prediction of therapy response in chronic rhinosinusitis with nasal polyps treated with Dupilumab - Danisman, Zeynep; Linxweiler, Maximilian; Kühn, Jan Philipp; Linxweiler, Barbara; Solomayer, Erich-Franz; Wagner, Mathias; Wagenpfeil, Gudrun; Schick, Bernhard; Berndt, Sabrina (Frontiers in Immunology, 2023)
Chronic Rhinosinusitis with nasal polyps (CRSwNP) is a common disease with high impact on patients’ life quality. If conservative and surgical treatment cannot control disease burden, biologicals e.g. Dupilumab can be considered. With the aim to select patients who benefit from this new treatment and to find a marker for therapy monitoring, we investigated the cellular composition of nasal mucosa of CRSwNP patients undergoing Dupilumab therapy using non-invasive nasal swab cytology. Twenty CRSwNP patients with the indication for Dupilumab therapy were included in this prospective clinical study. In total, five study visits were conducted with ambulatory nasal swabs every three months for 1 year starting with the beginning of treatment. Cytology samples were MGG (May-Gruenwald-Giemsa) stained and the percentage of ciliated, mucinous, eosinophil, neutrophil cells, and lymphocytes was analyzed. Additionally, an immunocytochemical (ICC) ECP-staining was performed to detect eosinophils. During each study visit the nasal polyp score, SNOT20-questionnaire, olfactometry, serum IgE-level and the blood eosinophil cell count were recorded. We analyzed the change of these parameters over one year and correlated MGG-/ICC-results with therapy response. In both MGG (p<0.0001) and ICC analysis (p<0.001) a significant decrease of eosinophils was seen under Dupilumab treatment. When dividing patients into a Eo-low- (<21%) and Eo-high- (≥21 %) group according to the percentage of pre-treatment eosinophils, Eo-high-group showed a greater change of eosinophils over time (∆17.82) compared to Eo-low-group (∆10.67). The polyp score, SNOT20-questionnaire, and total IgE concentration showed a significant decrease (p<0.0001). Nasal swab cytology is an easy-to-apply diagnostic method allowing detection and quantification of different cell populations within the nasal mucosa at a given time. Nasal differential cytology showed a significant decrease of eosinophils during Dupilumab therapy and can therefore be used as non-invasive method for monitoring therapy success of this cost intensive therapy and potentially can allow an optimized individual therapy management for CRSwNP patients. Since the validity of initial nasal swab eosinophil cell count as a predictive biomarker for therapy response was limited in our study, additional studies including larger number of participants will be necessary to further evaluate the potential benefits for clinical practice of this new diagnostic method.